AB0586 Role of particular class i mhc genotypes and haplotypes in determining different traits within the psoriatic arthritis phenotypes. (23rd January 2014) - Haroon, M.; Giles, J. T.; Winchester, R.; FitzGerald, O.
Abstract : Background: A rigorously ascertained psoriatic arthritis (PsA) cohort demonstrated considerable genetic heterogeneity and provided preliminary evidence that MHC genes determine quantitative traits within the PsA phenotype with different patterns of MHC effect. (Arth & Rheum 2012. 64: 1134). Objectives: To investigate any potential association of clinical phenotypes with already well characterised and quantified genotypes of PsA patients belonging to a genetically relatively homogeneous population Methods: A consecutive cohort of 283 PsA patients underwent detailed skin and rheumatologic assessments. We chose four traits to analyze - sacroiliitis, enthesitis, joint deformity and dactylitis. To examine their genotypic interaction, we assigned a score to each patient's allele and haplotype. +1 if an allele or haplotype was associated with a high risk for the trait, and -1 if it conferred a low risk in univariate analysis. Alleles or haplotypes not significantly associated with a trait were assigned "0", and the score summed assuming an additive risk model. Results: A total of 283 PsA patients [mean age 55±12 years; 47% male; mean PsA duration=19±9 years; 25% with sacroiliitis; 44.5% with radiographic erosions; 34% with enthesitis; 53% with dactylitis, 60% of this PsA cohort requiring TNFi therapy] were studied. The figure shows the frequency of each trait as a function of the risk score for the alleles and haplotypes associated with high or low risk and the average change in the odds of having each trait per 1 unit increase in the genotype risk score, e.g. the OR of developing enthesitis with an alleles/haplotypes genotype score of +2 to +4 was 13.9, p<0.001. Image/graph: Conclusions: HLA genotype importantly influences the clinical phenotype of psoriatic arthritis; and these phenotypes are likely the result of cis and trans interactions of multiple individual alleles. Disclosure of Interest: None Declared